Figures and tables from "Hybrid membrane distillation reverse electrodialysis configuration for water and energy recovery from human urine: An opportunity for off-grid decentralised sanitation." - Mercer, Edwina V.; McAdam, Ewan; Davey, Christopher J.; Pidou, Marc; Tyrrel, Sean; Williams, Leon; Jiang, Ying; Parker, Alison; Tierney, Ross; Azzini, Daniele; Eusebi, Anna (Cranfield University, 2019)
This data compiles the dataset required to generate the tables and figures for the paper - "Hybrid membrane distillation reverse electrodialysis configuration for water and energy recovery from human urine: An opportunity for off-grid decentralised sanitation."
Keywords: Reverse Electrodialysis'; 'urine'; 'Sanitation'; 'Membrane Distillation Membrane distillation'; 'Membrane and Separation Technologies'